Protocol for quantifying SA-β-gal activity as a measure of senescence in islets of a mouse model of type 1 diabetes - Hugo Lee; Peter J. Thompson; Feyza Engin (STAR Protocols, 2024)
Summary: A subpopulation of pancreatic beta cells becomes senescent during type 1 diabetes (T1D) progression, and removal of these populations protects against T1D in mice. Here, we present a protocol to measure senescence in murine pancreatic islet cells through analysis of senescence-associated β-galactosidase activity. We describe steps for staining with the fluorogenic substrate C12FDG and analysis by flow cytometry. Increased cell size is another marker of senescence and can also be concurrently measured in the same experiment.For complete details on the use and execution of this protocol, please refer to Lee et al.1 and Helman et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.